2017
DOI: 10.1016/j.joca.2017.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of non-surgical therapies for osteoarthritis of the hand: an update

Abstract: Hand OA is a complex area in which to study the efficacy of therapies. There has been an improvement in the overall design and conduct of RCTs, however, additional large RCTs with a more robust methodological approach specific to hand OA are needed in order to make clinically relevant conclusions about the efficacy of the diverse treatment options available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 96 publications
1
26
0
1
Order By: Relevance
“…This largely biases the findings of the review towards a European context, which may consequently influence its generalizability to other geographical locations. The present reviewers therefore report that perhaps the findings of this systematic review may not Interestingly, we observed from the literature, that our assumptions were consistent with a recent systematic review [40] that reported that despite the marked improvement in the overall design and conduct of RCTs, further large RCTs with more robust methodological approaches specific to hand OA are needed to make clinically relevant conclusions about the efficacy of the diverse treatment options available.…”
Section: Summary Of Evidencesupporting
confidence: 80%
See 1 more Smart Citation
“…This largely biases the findings of the review towards a European context, which may consequently influence its generalizability to other geographical locations. The present reviewers therefore report that perhaps the findings of this systematic review may not Interestingly, we observed from the literature, that our assumptions were consistent with a recent systematic review [40] that reported that despite the marked improvement in the overall design and conduct of RCTs, further large RCTs with more robust methodological approaches specific to hand OA are needed to make clinically relevant conclusions about the efficacy of the diverse treatment options available.…”
Section: Summary Of Evidencesupporting
confidence: 80%
“…The above findings are consistent with previous evidence [27], which reported that physiotherapy interventions lacked detailed information regarding the mode of delivery, intensity, frequency and duration. To identify the cause of this gap, we appraised some of the key "underpinning research evidence" [11,40,41,42] of the guidelines included in our systematic review. From this appraisal, we found that whilst some of the underpinning research evidence described the content of exercises which was not reported by the guidelines, majority provided limited or no content for guideline developers to report on subsequently.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…A wide range of OA serum or plasma biomarkers have been investigated in hand OA, which can provide insight into disease development. These biomarkers include various inflammatory markers, such as Creactive protein and adipokines, and markers of cartilage or bone homeostasis, such as type II collagen 149,150 . In one small sub-study of 18 patients from a 2016 hand OA clinical trial, serum IL-1 levels were associated with loss of hand function and radiological erosions 151 .…”
mentioning
confidence: 99%
“…Treatments commonly used prior to surgery include injections (cortisone, hyaluronate), analgesics, patient education in joint protection, strengthening exercises, assistive devices, and orthotics [21,22]. Few randomized clinical trials on conservative treatment of OAT have been published [22][23][24][25][26][27]. There is increasing evidence favoring multimodal manual treatment to reduce pain and ameliorate function in OAT patients [26,[28][29][30].…”
Section: Introductionmentioning
confidence: 99%